A smart pipet tip: Triboelectricity and thermoelectricity assisted in situ evaluation of electrolyte concentration. (August 2017) - Choi, Dongwhi; Tsao, Yu-Hsiang; Chiu, Che-Min; Yoo, Donghyeon; Lin, Zong-Hong; Kim, Dong Sung
Abstract: Pipet tips are commonly utilized laboratory tools to transfer adjustable volume of liquid in various fields of chemistry, biology and physics. Recently, we have reported that the ordinary pipetting procedure always involves spontaneous liquid-solid contact electrification, resulting in generation of net electrical charges on the dispensed solution and the inner surface of the polymeric pipet tip. In this study, a concept of a smart pipet tip is proposed to evaluate the electrolyte concentration of the dispensed solution by use of spontaneously generated electric signals during the ordinary pipetting procedure. The smart pipet tip possessing triboelectricity and thermoelectricity detecting modules is advantageous as it performs in situ evaluation of solution characteristics without any subsidiary solution handling process. The spontaneously generated electric signals are intensively investigated with the theoretical analyses. The proof-of-concept demonstration of the present smart pipet tip is shown for in situ prediction of morphology of nanoparticles during their synthetic reaction, which critically determines their catalytic activity. Graphical abstract: We demonstrate that the developed smart pipet tip composed of triboelectricity and thermoelectricity detecting modules is useful for the evaluation of solution characteristics and chemical reactions. Highlights: The present smart pipet tip enables in situ evaluation of solution characteristics. Firstly, the electrical charges inside the pipet tip is advantageously utilized. Multi-parametric effect on liquid-solid triboelectricity is effectively separated. The morphology of nanoparticles can be in situ predicted by using the smart pipet tip.